THE EFFECT OF WORK ENVIRONMENT AND WORK FACILITIES ON THE JOB SATISFACTION OF EDUCATORS AT SMK MITRA INDUSTRI MM2100 - Novita Sari Tanuwijaya; Manahan Tampubolon; Mesta Limbong (Indonesian Journal of Multidisciplinary Science, 2022)
Industry has a significant role in supporting Indonesian economy. Realizing this, the Ministry of Education and Culture collaborate with the Ministry of Industry and industrial factory create a synergy between the industrial world and vocational education to prepare human resources whose competence is in accordance with industrial needs. The Ministry of Education and Culture has collaborated with several vocational high school and one of them is SMK Mitra Industri MM 2100. This SMK whose management is carried out by industrial experts and companies in MM 2100 industrial estate have a curriculum that is in accordance with the wishes of the industry. As the designer of the curriculum, educators play a role in supporting the success of this vocational school. On this occasion the author will see how the success of this vocational school in managing the factors that become the school's input to achieve the success that has been achieved is how the influence of the work environment and work facilities. The results of the research can thus be used as evaluation material for schools and be a useful reference for other vocational schools as well. The research was conducted using quantitative methods with data collection using questionnaires distributed to 61 respondents of educators in SMK which were then processed using Microsoft Excel and SPSS. The results showed that there was a positive influence between the work environment (X1) and job satisfaction (Y) with an influence strength of 0.662, and there was a positive influence between work facilities (X2) and job satisfaction (Y) with an influence strength of 0.592. Furthermore, there is a relationship between the work environment (X2) and job satisfaction (Y) if work facilities (X2) are included as a control variable but the effect is weakened to 0.601. So this study suggests re-evaluating the work facilities provided whether it is necessary to make adjustments or increase the provision of work facilities based on current developments so that their influence is stronger in creating a positive work environment for educators. In addition, Vocational High Schools need to continue to innovate and improve to be ready to face the VUCA era in which we are required to be more agile.